ZAKAT SEBAGAI INSTRUMEN KEBIJAKAN FISKAL - Rahmat Ridwan; Randa Afri Putra; Putri Mufidatul Khairi (LPPM - STIE SAKTI ALAM KERINCI, 2023)
The article that the author writes contains several studies regarding Zakat as a Fiscal Instrument. In simple terms zakat can be interpreted as a person's obligation to his wealth and reach the nisab which is then intended for a group of people. While Instrument means a tool. And fiscal policy is a policy regarding state income and spending. That's a little description of zakat, instruments and fiscal policies. And this study aims to find out how zakat can be used as an instrument in fiscal policy. Therefore the author has a goal to know and understand about zakat. And not only that, this article also aims to find out and describe fiscal policy.